Mitochondrial dysfunction in diabetic nephropathy: insights and therapeutic avenues from traditional Chinese medicine - Zhao, Dan-mai; Zhong, Rui; Wang, Xiao-tian; Yan, Zhong-hong (Frontiers in Endocrinology, 2024)
Diabetic nephropathy (DN) is a microvascular complication of diabetes mellitus. The progressive damage to glomeruli, tubules, and interstitium in the kidneys can lead to the development of chronic kidney disease (CKD) and end-stage renal disease (ESRD). Most of the energy we need comes from mitochondria. Mitochondria are best known as the sites for production of respiratory ATP and are essential for eukaryotic life. The pathogenesis of DN involves a variety of factors, such as altered haemodynamics, oxidative stress, and inflammation, and studies from animal models suggest that mitochondrial dysfunction plays an important role in the development of DN. Traditional Chinese medicine (TCM) has a history of more than 2,500 years and has rich experience and remarkable efficacy in the treatment of DN. Recent studies have found that TCM may have great potential in regulating mitochondrial dysfunction in the treatment of DN. This review will elucidate the main causes of mitochondrial dysfunction and the relationship with DN, and explore in depth the potential mechanisms of TCM to protect the kidney by improving mitochondrial dysfunction. Current pharmacological treatments for patients with DN do not prevent the inevitable progression to ESRD. With the rich variety of Chinese herbs, TCM is expected to be the most promising candidate for the treatment of DN as we continue to learn more about the mechanisms of DN and incorporate the current advances in extraction techniques.